2018
DOI: 10.1055/a-0592-7219
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Power in Team Sports - Part 2: Aerobic and Anaerobic Energy Yields

Abstract: A previous approach to estimate the time course of instantaneous metabolic power and O consumption in team sports has been updated to assess also energy expenditure against air resistance and to identify walking and running separately. Whole match energy expenditure turned out ≈14% smaller than previously obtained, the fraction against the air resistance amounting to ≈2% of the total. Estimated net O consumption and overall energy expenditure are fairly close to those measured by means of a portable metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 12 publications
1
46
1
Order By: Relevance
“…Finally, we would like to point out that the approach described above does not take into consideration several specific characteristics of soccer, such as jumps, backwards running, running with the ball, kicking the ball or confronting an opponent. Nevertheless, as discussed in detail in the accompanying paper [12], we think that, in terms of the energetics of a match and provided that it is correctly implemented, this approach yields a picture closer to the "truth" than that emerging from more conventional approaches. ▶Fig.…”
Section: General Discussion and Conclusionmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, we would like to point out that the approach described above does not take into consideration several specific characteristics of soccer, such as jumps, backwards running, running with the ball, kicking the ball or confronting an opponent. Nevertheless, as discussed in detail in the accompanying paper [12], we think that, in terms of the energetics of a match and provided that it is correctly implemented, this approach yields a picture closer to the "truth" than that emerging from more conventional approaches. ▶Fig.…”
Section: General Discussion and Conclusionmentioning
confidence: 91%
“…We have previously shown that the energy cost of accelerated/decelerated running on flat terrain can be estimated on the basis of the biomechanical equivalence between accelerated/decelerated running on flat terrain and uphill/downhill running at constant speed [5] and that this approach can be applied to soccer and other team sports [13]. Indeed, by monitoring the players' speed at 18.18 Hz by means of a GPS system (GPEXE®), it is possible to estimate energy cost, overall energy expenditure and instantaneous metabolic power of any given player, from which the effective O₂ consumption can also be obtained, as shown in the accompanying paper [12]. However, in soccer as in many other team sports, several walking episodes are interspersed among running bouts.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSG) is controversial [9][10][11], it has been demonstrated that the MP analysis may be useful to properly assess the physical constraints and especially the high-intensity phases of professional players (i.e. match or training session) [6,8,[12][13][14]. Indeed, the high-intensity phases require an attention to proper monitoring of players' external workload, and are decisive moments that impact the matches [15,16].…”
Section: Monitoring Matches and Small-sided Games In Elite Young Soccmentioning
confidence: 99%
“…Recently, a metabolic power (MP) approach has been developed to estimate more precisely the energy expenditure of soccer players considering positive and negative accelerations, instantaneous running speed and mechanical parameters of the athletes [6][7][8]. The…”
Section: Introductionmentioning
confidence: 99%